An alternative approach for the decontamination of hospital settings. Issue 12 (December 2020) - Moccia, Giuseppina; Motta, Oriana; Pironti, Concetta; Proto, Antonio; Capunzo, Mario; De Caro, Francesco
Abstract: Background: The increasing emergence and spread of multiresistant microorganisms in hospital wards is a serious concern. Traditional protocols are often not sufficient to protect patients susceptible to serious and life-threatening infections, therefore new strategies for decontaminating hospital environments are crucial to reducing microbial transmission and the spread the nosocomial infections. The adoption of modern technologies is indicated to supplement traditional methods and to improve desired levels of surface disinfection. Aim: This work aims to report the development, implementation, and validation of cleansing and sanitizing procedure for critical clinical settings through the innovative use of disposable cloths pre-impregnated with solutions containing different active formulations and biocidal agents, relating to the areas to be treated (low, moderate, high-risk). Methods: The implementation and validation of the sanitizing system were conducted in different wards of two healthcare structures. The protocol for the study involved a structured selection of representative surfaces, such as the floor, bathroom, desk, and beds. Microbiological analyses were performed according to ISO 4833-1:2013. Findings: The efficiency of the proposed system was measured through the estimation of total microbial count values on the different surfaces before and after the sanitization operations by traditional methods and by the system described here. The results demonstrated a significant reduction in the microbial count that always fell below the threshold value. For the analyzed surfaces such as shower tray, bathroom floor, toilet edge, the traditional system had an effectiveness of less than 10%, whereas pre-impregnated cloths succeed to eliminate about 90% of the bacteria present. As an example, on the floor we observed a microbial count reduction from >42 to 10 CFU/11 cm 2 with the new method (76% of colonies were destroyed), while with the traditional one we have a reduction from >42 to 28 CFU/11 cm 2 (33% of microbial colonies). Moreover, the advantages of using this sanitization system are not limited to disinfecting surfaces and limiting cross-contamination but involve all activities related to the cleaning and disinfection operations, including the training and education of the operators and traceability of the operations. Conclusions: The innovative disinfection and cleaning protocol used in the present study proved to be a highly valuable alternative to the traditional cleaning procedures in healthcare settings for the sanitizing process of all kinds of surfaces. All tools were specifically designed to improve disinfection efficiency and to reduce the problems associated with traditional methods, such as preventing cross-contamination events, limiting the physical efforts of operators, and avoiding incorrect practices. Our findings add support to the knowledge that an effective sanitization procedure is critical in minimizing microorganisms' transmission and cross-contamination.